FSMP-09. FORMATE PROMOTES CANCER CELL INVASION AND METASTASIS VIA CALCIUM SIGNALING. (25th March 2021) - Delbrouck, Catherine; Pozdeev, Vitaly I; Oudin, Anais; Grzyb, Kamil; Neises, Laura; Kiweler, Nicole; Skupin, Alexander; Letellier, Elisabeth; Niclou, Simone P; Meiser, Johannes
Abstract: Serine catabolism via the folate cycle provides formate that is essential for nucleotide synthesis in proliferating cells. In addition to this canonical function to support biomass production in anabolic cells, we have recently demonstrated in vitro and in vivo that formate production in cancer cells is often in excess of the anabolic demand. This excess formate production is characterized by formate overflow and thus, net formate excretion into the tumor microenvironment. Interestingly, we observe increased rates of formate overflow upon different chemical perturbations that induce growth arrest. Thus, stressed cancer cells that encounter growth restriction such as upon chemotherapy, are often characterized by increased formate release rates. We demonstrated that such high formate levels in the extracellular space promote invasion of glioblastoma cells. Using ex vivo brain slice cultures and an orthotopic brain tumor model, we demonstrate that silencing MTHFD1L, the essential enzyme to enable formate overflow, results in decreased invasiveness of the tumor. Embarking from this observation, we investigated the underlying mechanism and now provide evidence that the formate-dependent increase of cell motility is mediated by an activation of Ca 2+ signaling. Activation of Ca 2+ signaling triggers integrin and matrix metallopeptidase (MMP) responses enabling the invasion process. Targeting either the Ca 2+ response or MMP release can suppress the formate dependent increase in invasion. Finally, we tested the effect of formate also in context of breast cancer where we were able to recapitulate our observation of increased invasiveness and, in this case, formate also promoted the metastatic potential. We conclude that excreted formate might serve as a cellular stress signal that represents a promotive trigger to support tumor escape mechanisms.